2017
DOI: 10.1016/j.crad.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow fat content is correlated with hepatic fat content in paediatric non-alcoholic fatty liver disease

Abstract: AIM To investigate the relationship between bone marrow fat content and hepatic fat content in children with known or suspected non-alcoholic fatty liver disease (NAFLD). MATERIALS AND METHODS This was an institutional review board-approved, Health Insurance Portability and Accountability Act (HIPAA)-compliant, cross-sectional, prospective analysis of data collected between October 2010 to March 2013 in 125 children with known or suspected NAFLD. Written informed consent was obtained for same-day research ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
3
12
1
Order By: Relevance
“…Indeed, NAFLD (especially NASH with varying amounts of liver fibrosis) exacerbates insulin resistance and causes the release of a variety of proinflammatory cytokines (e.g., interleukin‐6, tumor necrosis factor‐alpha) and bone‐influencing molecules (such as osteoprotegerin, osteocalcin, sclerostin, dickkopf‐related protein‐1, or procollagen type 1 N‐terminal propeptide), which may promote bone fragility and susceptibility to fracture over time . A recent study has also reported that lumbar spine bone marrow fat content (as measured by magnetic resonance imaging) is associated with increased hepatic fat content, independent of age, sex, BMI, and abdominal visceral fat mass in children with known or suspected NAFLD . However, more research is needed to better elucidate the complex pathophysiological links between NAFLD and low BMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, NAFLD (especially NASH with varying amounts of liver fibrosis) exacerbates insulin resistance and causes the release of a variety of proinflammatory cytokines (e.g., interleukin‐6, tumor necrosis factor‐alpha) and bone‐influencing molecules (such as osteoprotegerin, osteocalcin, sclerostin, dickkopf‐related protein‐1, or procollagen type 1 N‐terminal propeptide), which may promote bone fragility and susceptibility to fracture over time . A recent study has also reported that lumbar spine bone marrow fat content (as measured by magnetic resonance imaging) is associated with increased hepatic fat content, independent of age, sex, BMI, and abdominal visceral fat mass in children with known or suspected NAFLD . However, more research is needed to better elucidate the complex pathophysiological links between NAFLD and low BMD.…”
Section: Discussionmentioning
confidence: 99%
“…(10,(34)(35)(36) A recent study has also reported that lumbar spine bone marrow fat content (as measured by magnetic resonance imaging) is associated with increased hepatic fat content, independent of age, sex, BMI, and abdominal visceral fat mass in children with known or suspected NAFLD. (28) However, more research is needed to better elucidate the complex pathophysiological links between NAFLD and low BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible contributor to reduced bone formation is increased bone marrow adiposity, which is thought to inhibit osteoblast differentiation and enhance osteoclast differentiation . A recent study with 125 patients showed that bone marrow fat content was positively associated with hepatic fat content in children with known or suspected NAFLD . We assessed an index of bone marrow adiposity using gene expression of ap2 and ppar‐γ , markers of mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…There is an alarming increase in the incidence of obesity‐associated NAFLD among the pediatric population in the US; specifically, 30% of children are obese and obesity is maintained in 80% of adolescents through adulthood . A recent study has shown that hepatic fat content in children with known or suspected NAFLD positively associated with bone marrow fat content, which could also impact skeletal integrity . More studies are needed to explore the long‐term consequences of liver disease and NAFLD on bone health.…”
Section: Introductionmentioning
confidence: 99%